Implementing Situational Crime Prevention Theory in the Matter of Financial fraudulent - Nanang Shonhadji; Laila Saleh Marta; Ali Soebijanto; Febrina Ayu (Universitas Hayam Wuruk Perbanas, 2024)
Fraud and financial crime continue to pose significant challenges for private companies, making prevention efforts essential through the identification of their root causes. This study examines the relationship between situational crime prevention and financial fraud, with a focus on employee tenure as a moderating variable. An empirical research method was employed, with data collected from employees of PT Budi Jaya and its subsidiaries through questionnaires. A total of 60 valid responses were analyzed using WarpPLS. The findings reveal that situational crime prevention—measured through indicators such as minimal benefits, high risks, limited opportunities, and strict sanctions—has a significant negative impact on financial fraud. Additionally, the study demonstrates that employee tenure moderates the relationship between situational crime prevention measures and financial fraud. This research makes a theoretical contribution to situational crime prevention theory by incorporating the concept of rationalization, which fraud perpetrators often use to justify their actions. The study offers practical insights, suggesting that companies and regulators should implement robust internal control systems to minimize opportunities for fraud and establish clear, stringent rules and sanctions to deter fraudulent behavior.